CAUSES AND CONSEQUENCES OF PRESSURISATION IN LAVA DOME ERUPTIONS - Sparks R.S.J. (My University, 1997)
High total and fluid pressures develop in the interior of high-viscosity lava domes and in the uppermost parts of the feeding conduit system as a consequence of degassing. Two effects are recognised and are modelled quantitatively. First, large increases in magma viscosity result from degassing during magma ascent. Strong vertical gradients in viscosity result and large excess pressures and pressure gradients develop at the top of the conduit and in the dome. Calculations of conduit flow show that almost all the excess pressure drop from the chamber in an andesitic dome eruption occurs during the last several hundred metres of ascent. Second, microlites grow in the melt phase as a consequence of undercooling caused by gas loss. Rapid microlite growth can cause large excess fluid pressures to develop at shallow levels. Theoretically closed-system microlite crystallization can increase local pressure by a few tens of MPa, although build up of pressure will be countered by gas loss through permeable flow and expansion by viscous flow. Microlite crystallization is most effective in causing excess gas pressures at depths of a few hundred metres in the uppermost parts of the conduit and dome interior. Some of the major phenomena of lava dome eruptions can be attributed to these pressurization effects, including spurts of growth, cycles of dome growth and subsidence, sudden onset of violent explosive activity and disintegration of lava during formation of pyroclastic flows. The characteristic shallow-level, long-period and hybrid seismicity, characteristic of dome eruptions, is attributed to the excess fluid pressures, which are maintained close to the fracture strength of the dome and wallrock, resulting in fluid movement during formation of tensile and shear fractures within the dome and upper conduit.
Keywords: SHIELD VOLCANOES; PRESSURE; MAGMAS; EXPLOSIVE ERUPTIONS; MICROLITE; VISCOSITY